Death-related gastric necrosis after Laparoscopic Adjustable Gastric Banding in the early post-operative period - Vougiouklakis Theodore; Mitselou Antigoni; Fragkouli Kleio (BMC, 2010)
Abstract We report a case of a rare complication of Laparoscopic Adjustable Gastric Banding (LAGB) as a cause of death in the immediate post-operative period. The number of relevant reports and postmortem images presented in the literature is extremely restricted. Gastric necrosis may constitute a cause of death after LAGB in the early post-operative period. Postmortem examination reveals the extension of gastric ischemia and necrosis, responsible for the lethal outcome. To date, only one case of gastric necrosis after LAGB in the immediate post-operative period leading to death has been reported, according to authors' knowledge. The diagnosis of this complication may be delayed on the grounds of its rarity. In our opinion, surgeons should be aware of the clinical state implying gastric ischemia early after LAGB, so as to recognize and, in turn, to treat it promptly.